Three‐dimensional porous poly(propylene fumarate)‐co‐poly(lactic‐co‐glycolic acid) scaffolds for tissue engineering. Issue 9 (25th September 2018) - Wu, Wei; Liu, Xifeng; Zhou, Zifei; Miller, A. Lee; Lu, Lichun
Abstract: Three‐dimensional structural scaffolds have played an important role in tissue engineering, especially broad applications in areas such as regenerative medicine. We have developed novel biodegradable porous poly(propylene fumarate)‐ co ‐poly(lactic‐co‐glycolic acid) (PPF‐ co ‐PLGA) scaffolds using thermally induced phase separation, and determined the effects of critical parameters such as copolymer concentration (6, 8, and 10 wt %) and the binary solvent ratio of dioxane:water (78/22, 80/20, 82/18 wt/wt %) on the fabrication process. The cloud‐point temperatures of PPF‐ co ‐PLGA changed in parallel with increasing copolymer concentration, but inversely with increasing dioxane content. The compressive moduli of the scaffolds increased with greater weight composition and dioxane:water ratio. Scaffolds formed using high copolymer concentrations and solvent ratios exhibited preferable biomineralization. All samples showed biodegradation capability in both accelerated solution and phosphate‐buffered saline (PBS). Cell toxicity testing indicated that the scaffolds had good biocompatibility with bone and nerve cells, which adhered well to the scaffolds. Variations in the copolymer concentration and solvent ratio exercised a remarkable influence on morphology, mechanical properties, biomineralization, and biodegradation, but not on the cell viability and adhesion of the cross‐linked scaffolds. An 8 to 10 wt % solute concentration and 80/20 to 82/18 wt/wt dioxane:water ratio were the optimum parameters for scaffold fabrication. PPF‐ co ‐PLGA scaffolds thus possess several promising prospects for tissue engineering applications. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A:2507–2517, 2018.